Effects of Recreational GHB Use and Multiple GHB-Induced Comas on Brain Structure and Impulsivity - Raposo Pereira, Filipa; McMaster, Minni T. B.; Schellekens, Arnt; Polderman, Nikki; de Vries, Yvon D. A. T.; van den Brink, Wim; van Wingen, Guido A. (Frontiers in Psychiatry, 2020)
Background and Aims: Regular use of gamma-hydroxybutyrate acid (GHB) can induce GHB-induced comas. Other substance use disorders are associated with alterations in brain structure and impulsivity. Here, we aim to investigate if these are also modulated by either regular GHB-use or GHB-induced comas. Methods: In a sample of human males, structural and diffusion neuroimaging data were collected for 27 GHB users with ≥4 GHB-induced comas (GHB-Coma), 27 GHB users without GHB-induced comas (GHB-NoComa), and 27 polydrug users who never used GHB (No-GHB). Structural brain parameters were analyzed macroscopically using voxel-based morphometry (VBM), and microscopically using tract-based spatial statistics (TBSS) and tractography. Impulsivity was assessed with the Barrat Impulsivity Scale (BIS). Results: In comparison to the other two groups, the GHB-Coma group showed higher fractional anisotropy in the body of the corpus callosum and lower mean diffusivity in the forceps minor (i.e. whole-brain TBSS analysis). No macrostructural differences, nor microstructural differences as assessed with tractography, were observed. The GHB-Coma group also reported higher impulsivity, which was more strongly associated with white matter volume and fractional anisotropy in tracts involved in impulse control (post-hoc analysis). GHB-use per se was neither associated with differences in brain structure nor with impulsivity. Conclusions: The results suggest that multiple GHB-induced comas, but not GHB-use per se, are associated with microstructural alterations in white matter and with higher self-reported impulsivity, which in turn was associated with white matter tracts involved in impulse control.